X-ray spectral and variability properties of low-mass active galactic nuclei. Issue 3 (3rd January 2015) - Ludlam, R. M.; Cackett, E. M.; Gültekin, K.; Fabian, A. C.; Gallo, L.; Miniutti, G.
Abstract : We study the X-ray properties of a sample of 14 optically selected low-mass active galactic nuclei (AGN) whose masses lie within the range 10 5 –2 × 10 6 M⊙ with XMM–Newton . Only six of these low-mass AGN have previously been studied with sufficient quality X-ray data, thus, we have more than double the number of low-mass AGN observed by XMM–Newton with the addition of our sample. We analyse their X-ray spectral properties and variability and compare the results to their more massive counterparts. The presence of a soft X-ray excess is detectable in all five objects which were not background dominated at 2–3 keV. Combined with previous studies, this gives a total of eight low-mass AGN with a soft excess. The low-mass AGN exhibit rapid, short-term variability (hundreds to thousands of seconds) and long-term variability (months to years). There is a well-known anticorrelation between black hole mass and variability amplitude (normalized excess variance). Comparing our sample of low-mass AGN with this relation we find that all of our sample lie below an extrapolation of the linear relation. Such a flattening of the relation at low masses (below ∼10 6 M⊙ ) is expected if the variability in all AGN follows the same shape power spectrum with a break frequency that is dependent on mass. Finally, we also found two objects that show significant absorption in their X-ray spectrum, indicative of type 2 objects, although they are classified as type 1 AGN based on optical spectra.